Public and Private Interests in the Sphere of Administration of Vaccination in a Pandemic - Корнута, Людмила Михайлівна; Корнута, Л. М.; Корнута, Людмила Михайловна; Kornuta, Liudmyla M.; Kornuta, Liudmila; Дробуш, Ірина Вікторівна; Дробуш, І. В.; Дробуш, Ирина Викторовна; Drobush, Iryna; Шминдрук, Ольга Федорівна; Шминдрук, О. Ф.; Шминдрук, Ольга Федоровна; et al. (Universidad del Zulia Maracaibo : Venezuela, 2021)
COVID-19 has posed challenges to the global community at large and to jurisprudence in particular. In the current context, it is of paramount importance to find the best possible solutions in the field of legal regulation that help minimize the harmful effects of the global multisectoral crisis, save lives and restore the well-being of society. The work aims to clarify the theoretical problems in the legal status of medical innovations in the context of the COVID-19 pandemic. The subject of research is anticoronavirus innovations in the medical field. The research methods used were the dialectical method, the system method, the formal-legal method, the historical-legal method, and the structural method. As a result of this work, the current state of legal regulation of anti-ronavirus medical innovations was analysed, in particular the international legal framework, as well as national legislation in this area; contradictions in the observance of the balance of public and private interests under the conditions of a pandemic are revealed and, consequently, some ways of resolving them are suggested.

COVID-19 поставив виклик світовій спільноті в цілому і юриспруденції зокрема. У сучасному контексті надзвичайно важливо знайти найкращі можливі рішення у сфері правового регулювання, які допоможуть мінімізувати шкідливі наслідки глобальної багатогалузевої кризи, рятувати життя та відновлювати добробут суспільства. Робота спрямована на з’ясування теоретичних проблем правового статусу медичних інновацій в умовах пандемії COVID-19. Предметом дослідження є антикоронавірусні інновації в медичній сфері. Використаними методами дослідження були діалектичний метод, системний метод, формально-правовий метод, історико-правовий метод, структурний метод. У результаті проведеної роботи проаналізовано сучасний стан правового регулювання антикоронавірусних медичних інновацій, зокрема міжнародно-правову базу, а також національне законодавство у цій сфері; виявлено суперечності у дотриманні балансу державних і приватних інтересів в умовах пандемії, а отже, запропоновано деякі шляхи їх вирішення.
Drobush I. Public and Private Interests in the Sphere of Administration of Vaccination in a Pandemic / I. Drobush, L. Kornuta, O. Shmyndruk, O. Kurhanska, T. Polishchuk // Cuestiones Políticas. - Vol. 39. - No. 68. - Universidad del Zulia Maracaibo : Venezuela, 2021. - P. 476-490.
Keywords: medical innovation; intellectual property; international health crisis; COVID-19; public administration; медичні інновації; інтелектуальна власність; міжнародна криза охорони здоров'я; COVID-19; державне управління; Research Subject Categories::LAW/JURISPRUDENCE